Analisis Pengaruh Informasi Akuntansi dan Informasi Non Akuntansi Terhadap Pengambilan Keputusan Kredit - Datuk Maralelo Siregar (CERED Indonesia Institute, 2021)
The purpose of this study was to The problem in this study is whether accounting information can be used to predict a credit decision taken by the Bank. Meanwhile, non-accounting information is a control variable in this study. Therefore, this study aims to gather empirical evidence on the matter. This research took place at Bank Mandiri Branch Sidoarjo Achmad Yani. In accordance with the purpose of this study, multiple regression analysis model was used to test the research hypothesis regarding the effect of accounting information on credit decisions.The population in this study are all applications for working capital loans that have been approved by the Bank. The sample drawn is 50 credit applications whose credit has been approved by the Bank in 2020.The results of the study indicate that accounting information does not entirely influence credit decision making. Meanwhile, non-accounting information that has an influence on bank credit decisions is the value of the guarantee and the experience of the leader of the prospective debtor.